Approximate Solutions of Dynamic Problems for Rectangular Composite Plates - V. Pakosh; M. Marchuk (Engineering Transactions, 1997)
We study the problem of dynamic deformation of rectangular composite plates with the same type of boundary conditions along each side. Generalized theory of plates taking into account the compliance to transversal shear strains is used. The building method of an approximate analytical solution is proposed. We have obtained the numerical result for the case of the impact load acting on the rigidly fixed plate.